Enhancing Oil Recovery in the E Intisar Field: Gas Lift Valve Design and Injection Optimization for Well E-65 103E - A Case Study - Nourden Mohamed Abdelsadeg, (African Journal of Advanced Pure and Applied Sciences, 2026)
The efficient extraction of hydrocarbons from oil and gas reservoirs is a critical aspect of the petroleum industry. As reservoirs mature, natural pressure declines, making it increasingly challenging to recover the desired production rates. Artificial lift systems play an important role in enhancing production rates by providing the necessary energy to lift fluids to the surface. This paper focus on type of artificial lift which is Gas lift. Gas lift is widely used artificial lift technique that employs compressed gas injected downhole the the well tube or casing to reduce the hydrostatic pressure of the wellbore, thereby facilitating fluid flow to the surface. In this paper EIntisar Field Well E-65-103E is selected for the study. The main task in this study is to redesign a gas lift system for well E-65, a case study by using PIPESIM software. The main points obtained and determined using the software are number of gas lift valves needed to lift the wells up, also the depth of these valves distributed through the tubing and space between them. In addition to this, the amount of gas injected daily through these valves from casing to tubing. Finally, internal flow performance curves versus vertical lift performance curves for well E-65 were determined before and after the gas lift redesign as an indicator of increased productivity, as the liquid production rate before the gas lift redesign was 554 STB/d, The redesign process contributed to the injection of appropriate amounts of gas into the hole, which increased the liquid production rate to 688 STB/d through simulation using the PIPESIM program, thus improving the oil production rate by about 19.5% compared to the first design.